Molecular-Based Identification for Fish and Seafood Pathogenic Bacteria - Dwiyitno Dwiyitno (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2010)
Food infection and intoxication of fish products are common due to consumption of foodexposed by either pathogenic or toxin promoter bacteria. A number of pathogenic bacteria havebeen identified related to fish and seafood such as Vibrio parahaemolyticusand other Vibrios,Escherichia coli, Aeromonas spp., Salmonellaspp., Staphylococcus aureus, Listeriamonocytogenes, Clostridium botulinum, C. perfringens, and Shigellaspp. However, isolationand identification of pathogenic bacteria from fish and seafood are often difficult due to the highnumber of contaminating and indigenous bacteria, while numbers of pathogenic bacteria arerelatively low. In the last 3 decades, several molecular methods have been developed and adoptedas official standard to supplement classical method, such as polymerase chain reaction (PCR)and its applications. Besides its limitation, molecular based identification offers advantages asroutine or screening analytical protocol for pathogenic bacteria in fish and seafood products.